2015
DOI: 10.3928/01477447-20150105-53
|View full text |Cite
|
Sign up to set email alerts
|

Readmission Within 30 Days of Discharge After Hip Fracture Care

Abstract: The Affordable Care Act currently requires hospitals to report 30-day readmission rates for certain medical conditions. It has been suggested that surveillance will expand to include hip and knee surgery-related readmissions in the future. To ensure quality of care and avoid penalties, readmissions related to hip fractures require further investigation. The goal of this study was to evaluate factors associated with 30-day hospital readmission after hip fracture at a level I trauma center. This retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…According to different studies, age, time to surgery, male gender, BMI, functional dependence status, ASA grade, ICU stay, and length of initial hospitalization have been discussed in direct relation to readmission rates by several authors. [5,17,18] Eschbach et al reported that patients of advanced age with hip-related fractures showed neither a prolonged in-hospital nor ICU stay, and there was no significant relation between advanced age and the number and type of complications. [19] In the current study, univariate analysis of these factors revealed that age, pre-fracture mobility dependence, ASA grade ≥3, and ICU stay were significant patient-related risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to different studies, age, time to surgery, male gender, BMI, functional dependence status, ASA grade, ICU stay, and length of initial hospitalization have been discussed in direct relation to readmission rates by several authors. [5,17,18] Eschbach et al reported that patients of advanced age with hip-related fractures showed neither a prolonged in-hospital nor ICU stay, and there was no significant relation between advanced age and the number and type of complications. [19] In the current study, univariate analysis of these factors revealed that age, pre-fracture mobility dependence, ASA grade ≥3, and ICU stay were significant patient-related risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The burden of comorbidities has been demonstrated as significantly associated with a higher risk of readmission. [18] Active clinical problems at the time of discharge may also play a leading role as the potential source of complications and readmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the frequency of complications and readmissions seems to be higher when patients are discharged to a skilled nursing facility. 6 And finally, of course, the potential for a wide range of undesirable and potentially dangerous adverse events using opioid drugs is widely recognized.…”
Section: Classical Pain Managementmentioning
confidence: 99%